A method for preparing wear-resistant ceramic material
By combining potassium long stone, sodium long stone, kaolin and other materials with specific substances such as graphene, basalt fiber, and other substances such as graphene and basalt fiber, prepare the abrasion -resistant ceramic materials with high resistance strength, solving existing ceramic tile wear resistance and anti -folding resistance The problem of insufficient strength has achieved a significant improvement in the performance of ceramic materials.
Patent Information
- Application Number
- CN202411622484.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-14
AI Technical Summary
The wear resistance and flexural strength of existing ceramic tiles are insufficient, making it difficult to meet market demand.
Potassium long stone, sodium stones, kaolin, snake -grain stone, roasted talc, nano oxide, graphene, basalt fiber, polyoxyethylene ether, ollene triatefluorosyl derivative and solvents are mixed to prepare Diversified uniform slurry, spraying granules, suppression of molding, and sintering, making a wear -resistant ceramic material with high folding strength.
The abrasion resistance of ceramic materials is significantly improved and the resistance of folding is more than 65MPa, which meets the market's demand for high -performance ceramic materials.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramics, and in particular relates to a method for preparing a wear-resistant ceramic material. Background Art
[0002] Ceramic tiles are widely used in daily production and life. Existing ceramic tiles are generally made of feldspar, talc, calcite, and kaolin as raw materials through grinding, mixing, pressing, and calcining. However, this type of ceramic tile has the problem of poor wear resistance and insufficient flexural strength. In the prior art, the wear resistance and flexural strength of ceramic tiles are improved by adding kyanite and titanium dioxide as raw materials. However, the flexural strength of the obtained ceramic material or ceramic tile is difficult to exceed 64MPa, which greatly limits the use of ceramic materials and cannot meet market demand.
[0003] Therefore, there is an urgent need to provide a new method for preparing a wear-resistant ceramic material, and the wear-resistant ceramic material obtained by the preparation method has both good wear resistance and flexural strength. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a method for preparing a wear-resistant ceramic material. The wear-resistant ceramic material prepared by the method for preparing the wear-resistant ceramic material of the present invention has both good wear resistance and high flexural strength, for example, the flexural strength exceeds 65MPa.
[0005] The wear-resistant ceramic material of the present invention is obtained by mixing potassium feldspar, sodium feldspar, kaolin, serpentine, calcined talc, nano zirconium oxide, graphene oxide, basalt fiber, polyoxyethylene ether, fullerene trifluoromethyl derivative, and solvent to obtain a uniformly dispersed slurry, and then spray granulation, compression molding and sintering are performed to obtain the wear-resistant ceramic material. Among them, by using polyoxyethylene ether, sodium dodecyl sulfate and solvent, each component (potassium feldspar, sodium feldspar, kaolin, serpentine, calcined talc, nano zirconium oxide, graphene oxide, basalt fiber, fullerene trifluoromethyl derivative) is uniformly dispersed, which is helpful to obtain a wear-resistant ceramic material with uniform performance. The use of graphene oxide, basalt fiber and fullerene trifluoromethyl derivative in combination with other components significantly improves the wear resistance of the wear-resistant ceramic material obtained by sintering. Graphene oxide has a two-dimensional structural characteristic, basalt fiber has a one-dimensional structure, and fullerene trifluoromethyl derivative has a zero-dimensional structural characteristic. Through the interaction of these three specific substances, a stable spatial structure can be formed, so that the wear-resistant ceramic material has high flexural strength.
[0006] In addition, the specific content of each component helps dispersion during mixing and release stress during sintering and cooling.
[0007] The present invention provides a method for preparing a wear-resistant ceramic material, comprising the following steps:
[0008] By weight, 40 parts of potassium feldspar, 15-30 parts of sodium feldspar, 1-8 parts of kaolin, 1-8 parts of serpentine, 5-20 parts of calcined talc, 2-8 parts of nano zirconium oxide, 0.1-1 parts of graphene oxide, 0.1-0.8 parts of basalt fiber, 0.5-2.5 parts of polyoxyethylene ether, 0.1-0.8 parts of fullerene trifluoromethyl derivative, 0.1-2 parts of sodium dodecyl sulfate and 10-50 parts of solvent are mixed to obtain slurry, and then spray granulation is carried out to obtain a blank, and then compression molding is carried out to obtain a green body, and sintering is carried out to prepare the wear-resistant ceramic material.
[0009] Preferably, the solvent includes water, a fluorine-containing solvent and an ester. The combined use of the three solvents can make other raw material components dispersed evenly.
[0010] Preferably, the fluorine-containing solvent is at least one selected from 1,3,5-tris(trifluoromethyl)cyclohexane, 1,2-difluoroethane, and hexafluoroisopropanol.
[0011] Preferably, the ester includes at least one of methyl formate and ethyl acetate.
[0012] Preferably, the volume ratio of water to fluorinated solvent and ester in the solvent is 10:(0.1-3):(0.05-3).
[0013] Preferably, the fullerene trifluoromethyl derivative is selected from C 60 (CF3) 12 , C 60 (CF3) 14 , C 60 (CF3) 16 , C 60 (CF3) 18 At least one of .
[0014] Preferably, the basalt fiber has a diameter of 1-8 μm and a length of 1-5 mm.
[0015] Preferably, nano tungsten disulfide is added before adding the basalt fiber. Adding the nano tungsten disulfide first and then adding the basalt fiber helps to evenly disperse the nano tungsten disulfide.
[0016] Preferably, the mesh size of the nano tungsten disulfide is 300-500 mesh.
[0017] Preferably, the amount of nano tungsten disulfide added is 0.3-1 part. Adding a small amount of nano tungsten disulfide can adjust the crystal phase ratio of the wear-resistant ceramic material and promote the improvement of the flexural strength of the wear-resistant ceramic material.
[0018] Preferably, the sintering temperature is 1200-1300° C., and the sintering time is 30-70 minutes; further preferably, the sintering temperature is 1250-1280° C., and the sintering time is 40-70 minutes.
[0019] Preferably, the sintering is carried out by heating the temperature to 1200-1300° C. at a rate of 6-15° C. / min.
[0020] Preferably, the sintering further includes a cooling process.
[0021] Preferably, during the cooling process, the temperature is first cooled to 550-600°C at a rate of 12-15°C / min, then cooled to 100-180°C at a rate of 5-8°C / min, and finally cooled to room temperature at a rate of 3-5°C / min. At this specific staged cooling rate, the internal stress of the wear-resistant ceramic material is further released, which helps to improve the flexural strength of the wear-resistant ceramic material.
[0022] Preferably, a method for preparing a wear-resistant ceramic material comprises the following steps:
[0023] By weight, 40 parts of potassium feldspar, 20-25 parts of sodium feldspar, 3-6 parts of kaolin, 3-6 parts of serpentine, 6-15 parts of calcined talc, 5-8 parts of nano zirconium oxide, 0.5-1 part of graphene oxide, 0.5-0.8 parts of basalt fiber, 0.8-2.5 parts of polyoxyethylene ether, 0.1-0.8 parts of fullerene trifluoromethyl derivative, 0.1-2 parts of sodium dodecyl sulfate and 10-40 parts of solvent are mixed to obtain slurry, and then spray granulation is carried out to obtain a blank, and then compression molding is carried out to obtain a green body, and sintering is carried out to prepare the wear-resistant ceramic material.
[0024] The wear-resistant ceramic material can be designed into a brick shape during molding, and finally sintered to obtain a wear-resistant ceramic brick.
[0025] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0026] (1) The wear-resistant ceramic material of the present invention is obtained by mixing potassium feldspar, sodium feldspar, kaolin, serpentine, calcined talc, nano zirconium oxide, graphene oxide, basalt fiber, polyoxyethylene ether, fullerene trifluoromethyl derivative, and solvent to obtain a uniformly dispersed slurry, and then spray granulation, compression molding and sintering are performed to obtain the wear-resistant ceramic material. Among them, by using polyoxyethylene ether, sodium dodecyl sulfate and solvent, each component (potassium feldspar, sodium feldspar, kaolin, serpentine, calcined talc, nano zirconium oxide, graphene oxide, basalt fiber, fullerene trifluoromethyl derivative) is evenly dispersed, which helps to obtain a wear-resistant ceramic material with uniform performance. The use of graphene oxide, basalt fiber and fullerene trifluoromethyl derivative in combination with other components significantly improves the wear resistance of the wear-resistant ceramic material obtained by sintering. Graphene oxide has a two-dimensional structural characteristic, basalt fiber has a one-dimensional structure, and fullerene trifluoromethyl derivative has a zero-dimensional structural characteristic. Through the interaction of these three specific substances, a stable spatial structure can be formed, so that the wear-resistant ceramic material has high flexural strength.
[0027] (2) Under the specific staged cooling rate of the present invention, it helps to further release the internal stress of the wear-resistant ceramic material and helps to improve the flexural strength of the wear-resistant ceramic material.
[0028] (3) Adding a small amount of nano tungsten disulfide can adjust the crystal phase ratio of the wear-resistant ceramic material and improve the flexural strength of the wear-resistant ceramic material. DETAILED DESCRIPTION
[0029] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0030] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0031] The potassium feldspar, sodium feldspar, kaolin, serpentine, calcined talc, and graphene oxide particles used below can pass through a 200-300 mesh sieve.
[0032] The diameter of basalt fiber is 2-4 μm and the length is 1-2 mm.
[0033] Example 1: Preparation of wear-resistant ceramic material
[0034] A method for preparing a wear-resistant ceramic material comprises the following steps:
[0035] By weight, 40 parts of potassium feldspar, 18 parts of sodium feldspar, 4 parts of kaolin, 3 parts of serpentine, 12 parts of calcined talc, 5 parts of nano zirconium oxide, 0.3 parts of graphene oxide, 0.4 parts of basalt fiber, 1 part of polyoxyethylene ether, 1 part of fullerene trifluoromethyl derivative (C 60 (CF3) 12 ) 0.4 parts, 0.5 parts of sodium dodecyl sulfonate, and 35 parts of solvent (the solvent consists of 30 parts of water, 3 parts of 1,3,5-tris(trifluoromethyl)cyclohexane, and 2 parts of methyl formate) are mixed and stirred at a stirring speed of 800 rpm for 60 minutes to obtain a slurry, which is then spray granulated to obtain a blank, which is then pressed to obtain a green body, and the temperature is raised to 1250°C at a rate of 12°C / min and sintered for 60 minutes, and then naturally cooled to room temperature to obtain a wear-resistant ceramic material.
[0036] Example 2: Preparation of wear-resistant ceramic material
[0037] A method for preparing a wear-resistant ceramic material comprises the following steps:
[0038] By weight, 40 parts of potassium feldspar, 17 parts of sodium feldspar, 3 parts of kaolin, 5 parts of serpentine, 15 parts of calcined talc, 6 parts of nano zirconium oxide, 0.5 parts of graphene oxide, 0.3 parts of basalt fiber, 1.5 parts of polyoxyethylene ether, and fullerene trifluoromethyl derivative (C 60 (CF3) 12 ) 0.3 parts, 0.4 parts of sodium dodecyl sulfate, and 30 parts of solvent (the solvent consists of 25 parts of water, 3 parts of 1,2-difluoroethane, and 2 parts of methyl formate) are mixed and stirred at a stirring speed of 900 rpm for 40 minutes to obtain a slurry, which is then spray granulated to obtain a blank, which is then pressed to obtain a green body, and the temperature is raised to 1260°C at a rate of 12°C / min and sintered for 65 minutes, and then naturally cooled to room temperature to obtain a wear-resistant ceramic material.
[0039] Example 3: Preparation of wear-resistant ceramic material
[0040] A method for preparing a wear-resistant ceramic material comprises the following steps:
[0041] By weight, 40 parts of potassium feldspar, 18 parts of sodium feldspar, 4 parts of kaolin, 3 parts of serpentine, 12 parts of calcined talc, 5 parts of nano zirconium oxide, 0.3 parts of graphene oxide, 0.5 parts of nano tungsten disulfide, 0.4 parts of basalt fiber (nano tungsten disulfide is added before adding basalt fiber), 1 part of polyoxyethylene ether, 1 part of fullerene trifluoromethyl derivative (C 60 (CF3) 12) 0.4 parts, 0.5 parts of sodium dodecyl sulfonate, and 35 parts of solvent (the solvent consists of 30 parts of water, 3 parts of 1,3,5-tris(trifluoromethyl)cyclohexane, and 2 parts of methyl formate) are mixed and stirred at a stirring speed of 800 rpm for 60 minutes to obtain a slurry, which is then spray granulated to obtain a blank, which is then pressed to obtain a green body, and the temperature is raised to 1250°C at a rate of 12°C / min and sintered for 60 minutes, and then naturally cooled to room temperature to obtain a wear-resistant ceramic material.
[0042] Example 4: Preparation of wear-resistant ceramic material
[0043] A method for preparing a wear-resistant ceramic material comprises the following steps:
[0044] By weight, 40 parts of potassium feldspar, 18 parts of sodium feldspar, 4 parts of kaolin, 3 parts of serpentine, 12 parts of calcined talc, 5 parts of nano zirconium oxide, 0.3 parts of graphene oxide, 0.4 parts of basalt fiber, 1 part of polyoxyethylene ether, 1 part of fullerene trifluoromethyl derivative (C 60 (CF3) 12 ) 0.4 parts, 0.5 parts of sodium dodecyl sulfonate, and 35 parts of solvent (the solvent consists of 30 parts of water, 3 parts of 1,3,5-tris(trifluoromethyl)cyclohexane, and 2 parts of methyl formate) are mixed and stirred at a stirring speed of 800 rpm for 60 minutes to obtain a slurry, which is then spray granulated to obtain a blank, which is then pressed to obtain a green body, and the temperature is increased to 1250°C at a rate of 12°C / min and sintered for 60 minutes, and then first cooled to 550°C at a rate of 13°C / min, then cooled to 150°C at a rate of 6°C / min, and finally cooled to room temperature at a rate of 4°C / min to obtain a wear-resistant ceramic material.
[0045] Comparative Example 1
[0046] Compared with Example 1, the difference of Comparative Example 1 is that the basalt fiber in Example 1 is replaced by an equal amount of carbon fiber, and other raw materials and processes are the same as those in Example 1.
[0047] Comparative Example 2
[0048] Compared with Example 1, the difference of Comparative Example 2 is that the graphene oxide in Example 1 is replaced by an equal amount of hexagonal boron nitride, and other raw materials and processes are the same as those in Example 1.
[0049] Comparative Example 3
[0050] Compared with Example 1, the difference of Comparative Example 3 is that an equal amount of Tween 80 is used to replace the sodium dodecyl sulfate in Example 1, and other raw materials and processes are the same as those in Example 1.
[0051] Product effect testing
[0052] The wear-resistant ceramic materials prepared in Examples 1-4 and the wear-resistant ceramic materials prepared in Comparative Examples 1-3 were taken as test samples. The size of the samples was set to 300mm*300mm*6mm. The wear resistance of the samples was tested according to GB / T12988-2009, and the flexural strength of the samples was tested according to GB / T2542-2012 "Test Methods for Wall Bricks". The results are shown in Table 1.
[0053] Table 1
[0054]
[0055] It can be seen from Table 1 that the wear resistance and flexural strength of the wear-resistant ceramic material prepared in the embodiment of the present invention are significantly better than those in Comparative Examples 1-3.
[0056] It can be seen from Example 1 and Comparative Example 1 that basalt fiber cannot be simply replaced by other fibers, such as carbon fiber. This is mainly because the unique structure and chemical composition of basalt fiber enable basalt fiber to be more evenly distributed in the wear-resistant ceramic material system of the present invention, thereby improving the wear resistance and flexural strength of the wear-resistant ceramic material.
[0057] It can be seen from Example 1 and Comparative Examples 2-3 that hexagonal boron nitride cannot replace graphene oxide, and Tween 80 cannot replace sodium dodecyl sulfate. The reason may be that graphene oxide can have better dispersibility with fullerene fluoride and other components, and sodium dodecyl sulfate, as a specific surfactant, significantly improves the dispersion uniformity of each component.
Claims
1. A method for preparing a wear-resistant ceramic material, characterized in that: The following steps are involved: By weight, 40 parts of potassium feldspar, 15-30 parts of sodium feldspar, 1-8 parts of kaolin, 1-8 parts of serpentine, 5-20 parts of calcined talc, 2-8 parts of nano zirconium oxide, 0.1-1 parts of graphene oxide, 0.1-0.8 parts of basalt fiber, 0.5-2.5 parts of polyoxyethylene ether, 0.1-0.8 parts of fullerene trifluoromethyl derivative, 0.1-2 parts of sodium dodecyl sulfate, and 10-50 parts of solvent are mixed to obtain a slurry, and then spray granulation is performed to obtain a blank, and then compression molding is performed to obtain a green body, and sintering is performed to obtain the wear-resistant ceramic material; The solvent consists of water, a fluorine-containing solvent and an ester; The fluorinated solvent is selected from at least one of 1,3,5-tris(trifluoromethyl)cyclohexane, 1,2-difluoroethane, and hexafluoroisopropanol; The ester is selected from at least one of methyl formate and ethyl acetate; The volume ratio of water to fluorinated solvent and ester in the solvent is 10:(0.1-3):(0.05-3); The fullerene trifluoromethyl derivative is selected from C 60 (CF3) 12 , C 60 (CF3) 14 , C 60 (CF3) 16 , C 60 (CF3) 18 At least one of; The sintering process also includes a cooling process; During the cooling process, the temperature is first cooled to 550-600° C. at a rate of 12-15° C. / min, then cooled to 100-180° C. at a rate of 5-8° C. / min, and finally cooled to room temperature at a rate of 3-5° C. / min.
2. The preparation method according to claim 1, characterized in that: The basalt fiber has a diameter of 1-8 μm and a length of 1-5 mm.
3. The preparation method according to claim 1, characterized in that: The sintering temperature is 1200-1300° C., and the sintering time is 30-70 minutes.
Citation Information
Patent Citations
Preparation method of porcelain tiles with high flexural strength
CN106495664A
Wear-resistant domestic ceramic product and preparation method thereof
CN111574055A